Translation studies in the Philippines navigating a multilingual archipelago - Bacolod, Mary Ann G.; Moratto, Riccardo 1985- (Abingdon, Oxon Routledge, Taylor & Francis Group, 2024)
"The contributors to this book examine the state, development, issues, practices and approaches to translation studies in the Philippines. The Philippines is a highly multilingual country, with many indigenous languages and regional dialects spoken alongside foreign imports, particularly English and Spanish. Professor Moratto, Professor Bacolod, and their contributors analyse the different roles that translation plays across an extensive range of areas, including disaster mitigation, crisis communication, gender bias, marginalization of Philippine languages, empowering communities, national consciousness, and views on sex, gender, and sexuality. They look at a range of different types of translation, from the translation of biblical texts to audio-visual translation, and machine translation. Emphasising the importance of translation as an interdisciplinary field, they use a variety of analytic lenses, including anthropological linguistics, forensic linguistics and performance arts, among others. A comprehensive resource for scholars and practitioners of translation, as well as a valuable reference for scholar across a wider range of humanities and social science disciplines in examining the culture and society of the Philippines"--
A concise history of translation in the Philippines / Naidyl Isis Bautista and Anna Marie Sarmiento-Sibayan -- Translation and interpreting education in the Philippines: a preliminary country profile / Marlon James Sales -- Performing disappearance and resurfacing: viewing the world through theater translation in the academe / Vladimeir B. Gonzales -- Beyond constraints: advancing linguistic consensus in Filipino subtitling / Michael Manahan -- Necessary infidelity: obligatory shifts in translating audiovisual texts for children / Honeylet E. Dumoran -- Gender bias in machine translation: the case of Filipino-English translation in Google Translate / Divine Angeli Endriga and Francisco Rosario, Jr. -- The biblical, the moral, and the legal: juxtaposing Filipino/Tagalog translations of biblical passages and local views on sex, gender, and sexuality / Jem R. Javier and Madilene B. Landicho -- On the translatability of Filipino modals and its impact on disaster communication / Mary Ann G. Bacolod -- Lost for words: the untranslatability of some Tagalog words and phrases / Jesus Federico C. Hernandez.
Includes bibliographical references and index.
CSSP-9675f donated by the Department of Linguistics.
Keywords: Translating and interpreting -- Philippines